Prevalence of Diabetes Mellitus and Awareness of Its Management among Tailors in Urban India - Begum, Nasreen; Fatima, Saadia (Al-Sihah : The Public Health Science Journal, 2024)
The rising diabetes prevalence in developing countries highlights a critical public health challenge linked to lifestyle changes and limited awareness of disease management. This study addresses the gap in understanding diabetes prevalence and management knowledge among sedentary occupational groups, such as tailors. This study aims to assess the prevalence of Diabetes Mellitus (DM) and evaluate knowledge regarding its management among tailors in Hyderabad. This community-based cross-sectional study assessed the prevalence of DM and evaluated knowledge about its management among tailors in Hyderabad, a group particularly at risk due to their sedentary work environments and limited awareness of diabetes management. Data were collected from 170 tailors aged 30–60 years across four localities in Hyderabad using a structured questionnaire and random blood glucose level checks. Results indicated that 58.8% of participants had normal glucose levels, 25.3% were pre-diabetic, and 15.9% were diabetic. Diabetes (19.4%) and hypertension (22.9%) were common, though only 37.1% adhered to regular medication. Irregular dietary habits were noted, with 61.8% skipping meals occasionally and 45% consuming outside food monthly. The mean blood glucose level was 146.85 mg/dL (SE: 3.92 mg/dL), with 97.1% consuming tea or coffee daily and 48.2% eating street food monthly. This study highlighted that Tailors, who tend to have sedentary work environments, are at particular risk due to a lack of awareness about diabetes, its management, proper nutrition normal Blood glucose, values and complications of DM.